Post-Prohibition Da'wah of Hizb ut-Tahrir Indonesia and Islamic Defenders Front - Mohammad Taufiq Rahman (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2023)
In 2017 the Indonesian government has officially banned two Islamic da'wah movements, HTI (Hizbut Tahrir Indonesia) and FPI (Islamic Defenders Front). These two da'wah movements are considered to be contrary to Pancasila ideology because they want to establish an Islamic state (Khilafah) in Indonesia. The focus of this research was carried out in the branch areas of HTI and FPI, namely in West Java and Banten. The data in this paper come from direct observation, in-depth interviews and documentation review. This paper finds differences in the pattern of the dakwah movements of HTI and FPI after they were disbanded, both in the dissemination of ideas and in the pattern of recruitment. HTI implemented a massive migration in preaching the idea of a khilafah from direct (offline) efforts to indirect (online) efforts. In its recruitment, HTI continues to maintain its conventional efforts through face-to-face preaching (Daurah), with the addition of using wing organizations as its spearhead. Meanwhile, the decline in the da'wah movement occurred in FPI, mainly due to the absence of the Grand Imam Rizieq Shihab and the loss of elite support for them. Even so, FPI continues to maintain its da'wah activities by disseminating its ideas through recitations at its activist headquarters, mosques and Islamic boarding schools. This research can contribute to the enrichment of the analysis of the hidden da'wah movement that occurs in the field, especially with the front stage and back stage approaches of Erving Goffman.